Goethe dan Aspek Multikultural Sastra Dunia - Lilawati Kurnia (HISKI, 2006)
When we use the term ‘Word Literature’, what comes into our minds is the meaning of the two words, what is meant by World – Literature? We can browse through the internet and try to find the meaning of this phrase in the cyber world, but can all definitions and lists of works from the many writers in the sites actually be acknowledged as World Literature? Moreover, if we try to explore the two words, does ‘literature’ only refer to literary works or all kinds of literature including books? The next word is ‘world’ of course has its own problem because we do not actually kniw whether it means the whole world in which every single literary work on earth is considered as world literature or it only refers to certain parts of the world like Europe and America.The phrase Weltliteratur was first articulated by a German Writer, Wieland, in the contect of world culture that privileges literary works in order to bring people to the world. It was quite different when Goethe used this phrase in his letter to Karl Streckfub, a translator of Italian classical works on 27 January 1927, and Goethe used that phrase again in his conversation with Johann Peter Eckermann, a young man who did some internship with him, on 31 January 1831. Goethe used the word Welt in a context of literature beyond the national context, literature outside German across national boundaries. Goethe articulated it by saying:“I am more convinced,” Goethe remarked, “that poetry is the universal possession of mankind, revealing itself everywhere and at all times in hundreds and hundreds of men… I therefore like to look about me in foreign nations, and advise everyone to do the same. National literature is now a rather unmeaning term; the epoch of world literature is at hand, and everyone must strive to hasten its approach.”The term used by Goethe gives out a modern sense which suits the globalize era where we live now. In this case, Goethe seemed to be ahead of his time in making a literary contribution.